Aerodynamics of badminton shuttlecock: Characterization of flow around a conical skirt with gaps, behind a hemispherical dome - Lin, C. S. A.; Chua, C. K.; Yeo, J. H. (Journal of Wind Engineering and Industrial Aerodynamics, 2014)
Highlights